2013
DOI: 10.1080/14786419.2013.832676
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling driven analysis ofSalsolaspecies and their anti-acetylcholinesterase potential

Abstract: Over 100 species of the genus Salsola are distributed in dry, arid parts of Asia, Europe and Africa, of which many species are recognised as antifungal, anticancer, antihypertensive and anthelmintic agents. Egyptian Salsola received scant characterisation of either its phytochemical composition or its biological effects. In this study, the metabolite profiles of two Salsola species viz. S. vermiculata and S. tetrandra were characterised in the aerial portions and root via ultra-performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…Other studies indicated that also phenolic compounds such as quercetin possess significant AChE inhibitory properties, suggesting a role for inhibition of AChE in the analyzed extracts [ 30 ]. N-ferulyl tyramine demonstrated a moderate inhibition activity on AChE when tested as a pure compound [ 31 ], while extracts of Salsola vermiculata L., rich in N-feruloyl tyramine, exert significant AChE inhibition [ 32 ]. Overall, the bibliographic data indicate that AChE inhibitory activity may be related to the different classes of compounds detected in A. subhirsutum .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies indicated that also phenolic compounds such as quercetin possess significant AChE inhibitory properties, suggesting a role for inhibition of AChE in the analyzed extracts [ 30 ]. N-ferulyl tyramine demonstrated a moderate inhibition activity on AChE when tested as a pure compound [ 31 ], while extracts of Salsola vermiculata L., rich in N-feruloyl tyramine, exert significant AChE inhibition [ 32 ]. Overall, the bibliographic data indicate that AChE inhibitory activity may be related to the different classes of compounds detected in A. subhirsutum .…”
Section: Resultsmentioning
confidence: 99%
“…: S. inermis) is also considered a glycine-betaine accumulator. Various Salsola species, including the species S. soda, have been examined for their phytochemical composition, showing the presence of alkaloids, flavonoids, saponins, coumarins, and sterols [171][172][173]. The shoots contain flavonoid glycosides and triterpenoid saponins [174].…”
Section: Biochemical Traitsmentioning
confidence: 99%
“…Genus Salsola is common in arid, semi-arid, and temperate regions worldwide (Rasheed et al 2013;Chauhan et al 2018). The exact number of species that falls under this genus has not been clearly established as yet.…”
Section: Genus Salsolamentioning
confidence: 99%